Genetic Background of a Recurrent Unusual Combined Form of Retinal Vein Occlusion: A Case Report - Kajo Bucan; Ivna Plestina Borjan; Ivona Bucan; Martina Paradzik Simunovic; Ivan Borjan (Case Reports in Ophthalmology, 2018)
The authors report a rare case of nonischemic branch retinal vein occlusion and nonischemic hemiretinal vein occlusion in a patient with impaired fibrinolysis. A 61-year-old woman presented to the Department of Ophthalmology, Clinical Hospital Center Split, Croatia, with acute blurring of vision in the right eye (RE) due to branch retinal vein occlusion. Ophthalmologic evaluation revealed a best corrected visual acuity (BCVA) of 0.02 in the RE and of 1.0 in the left eye. Ophthalmoscopy and fluorescein angiography of the RE demonstrated signs of nonischemic branch retinal vein occlusion. She was otherwise healthy and had no other ocular and systemic diseases. She was treated with 3 consecutive intravitreal applications of anti-vascular endothelial growth factor (anti-VEGF; bevacizumab) due to cystoid macular edema with full resolution of the intraretinal fluid and improvement of the BCVA to 0.9. After 8 months, she presented again with acute blurring of vision in the same (right) eye with a BCVA of 0.5. Ophthalmoscopy and fluorescein angiography of the RE indicated nonischemic hemiretinal vein occlusion. She was treated with a single intravitreal application of anti-VEGF (ranibizumab) due to macular edema. Full resolution of the intraretinal fluid and improvement of the BCVA to 0.9 were achieved. A laboratory workup was performed to rule out all known causes of retinal venous occlusive disease, which showed negative results. A molecular analysis showed the gen of thrombophilia – plasminogen activator inhibitor (PAI)-1 4G/5G polymorphism genotype – as the only risk factor for retinal venous occlusive disease in our patient.